2018
DOI: 10.18805/lr-3837
|View full text |Cite
|
Sign up to set email alerts
|

Seed bio-priming of green gram with Rhizobium and levels of nitrogen and sulphur fertilization under sustainable agriculture

Abstract: The experiment was laid out in a factorial randomized block design comprising eighteen treatment combinations of three levels of N (0, 10 and 20 kg ha -1 ), three levels of S (0, 10 and 20 kg ha -1 ) and two levels of biofertilizer (seed bio-priming and without Rhizobium) which were replicated three times. The results indicated that plot with the application of N and S @ 20 kg ha -1 gave significantly (p< 0.05) higher seed yield (~ 32 and 21%) and stover yield (~ 16 and 18%) as compared to control plot, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The present study revealed that the rhizobial strain MR 63 produced the maximum yield under both the drought and irrigated environment (Chart 2). Similar response of rhizobial inoculation induced yield improvement was reported by Choudhary et al (2019) and Tena et al (2016).…”
Section: Resultssupporting
confidence: 84%
“…The present study revealed that the rhizobial strain MR 63 produced the maximum yield under both the drought and irrigated environment (Chart 2). Similar response of rhizobial inoculation induced yield improvement was reported by Choudhary et al (2019) and Tena et al (2016).…”
Section: Resultssupporting
confidence: 84%
“…The higher yield in summer green gram following CT rice and wheat can be attributed to a combination of interconnected factors encompassing residue decomposition and nutrient availability, effective weed suppression, enhanced soil aeration and root penetration, better pest and disease management, and soil moisture conservation [79,80]. CT incorporates crop residues, promoting their decomposition and releasing nutrients that are readily available for the subsequent crop, enhancing the growth, yield, and yield-attributing characteristics of summer green gram [81]. Additionally, CT aids in effective weed control by burying weed seeds and disrupting their germination, reducing competition and providing the summer green gram crop with a competitive advantage [50,59].…”
Section: Crop Yieldmentioning
confidence: 99%